Genocidas ir rezistencija Nr. 20(2) - Brandišauskas, Valentinas; Bubnys, Arūnas; Smolskutė, Žaneta; Burinskaitė, Kristina; Banionis, Juozas; Jansons , Ritvars; Rahi-Tamm , Aigi; Juodis, Darius; Maripuu, Meelis; Anušauskas, Arvydas; Woycicki, Kazimierz; Zalite, Indulis; et al. (Genocidas ir rezistencija, 2006)
Pilnas leidinys (nuskenuota poprierinė versija)